External column lengthening with peek cage and modified single approach - Yearson, Diego; Melendez , Ignacio; Anain , Federico; Siniscalchi , Santiago; Drago , Juan (Journal of the Foot & Ankle, 2021)
Objective: To show the results obtained with the treatment of stage 2B flatfoot according to Myerson classification (reducible and flexible), through external column lengthening with interposition of a peek cage filled with spongious graft taken from the same calcaneus, without osteosynthesis, combined with medial slide calcaneal osteotomy with step plate, both using the a single approach. Medial time was associated with latero-lateral transfer of common flexor tendon of toes to posterior tibial. Methods: Sixteen patients were assessed from 2015 to 2018, of which 11 were women and 5 were men. In all cases, surgery was performed with a first lateral time for osteotomies and a second time for tendon repair. Mean patients’ follow-up was 28 months. Results: All patients achieved consolidation of both osteotomies at nearly 12 postoperative weeks. No patient presented signs of peek cage migration due to lack of stability or dorsal cutaneous nerve branch injuries resulting from this modified single approach. Two patients evolved with wound dehiscence and only one with calcaneocuboid pain so far. No patient required reoperation. Conclusion: The modified single tuberosity approach for the two osteotomies has shown to be a simple procedure that prevents damages to dorsal cutaneous nerve branches described with dorsal approach. Leve lof Evidence IV; Therapeutic Studies; Case Series.